Evidence for Vertical Transmission of Babesia odocoilei (Piroplasmida: Babesiidae) in Ixodes scapularis (Acari: Ixodidae). Issue 6 (3rd May 2021) - Zembsch, T E; Bron, G M; Paskewitz, S M
Abstract: Limited evidence suggests that the cervid parasite, Babesia odocoilei, is transovarially transmitted from adult female Ixodes scapularis Say to offspring. The prevalence of B. odocoilei in unfed larval I. scapularis and whether vertical transmission is crucial to pathogen maintenance are currently unknown. To investigate these questions, 275 unfed larvae from two Wisconsin counties were tested for B. odocoilei genetic material. Sixteen of 29 pools were positive for the parasite. The maximum likelihood estimation for overall larval infection prevalence was 7.8% (95% confidence interval: 4.7–12). This vertically acquired infection appears to be sustained transstadially in nymphal ticks the following year; however, our relatively small sample and replicate size warrants additional evaluation. Our study revealed further evidence of vertical transmission, a low and consistent infection prevalence in larvae, and the potential importance of vertical transmission in B. odocoilei maintenance.